Imposition of Criminal Sanctions in Online Loan Collection Activities Related to Theft of Personal Data - Sugiawan, Fricila Anggitha; Rukmana, Kevin Anandita; Muzacky, Ahmad (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
Globalization is growing rapidly affecting existing technology making many conveniences for society. bring positive and negative impacts in society. Slowly all forms of activity that were previously carried out manually are changing technology. This is also used by startup companies engaged in the fintech peer 2 peer lending or Pinjol business. consumer and public complaints about the theft of personal data on consumer loans, illegal access to consumer phone contact numbers, and also billing with threats and sexual harassment through social media belonging to consumers and relatives and families of consumer loans. Moreover, there are many illegal loan companies that trap their victims with high-interest loans that borrowers are unable to repay. This research uses a prescriptive legal method and examines law as a norm with misconceptions about legal protection. Secondary data becomes the main data. The specifications used are descriptive specifications. Theft of personal data with the aim of making threats and damaging a person's dignity is a crime that needs to be anticipated by Indonesian law.